Processes of institutionalization of non-Catholic chaplaincy and spiritual aide in public hospitals of Argentina - Gabriela Irrazábal (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2018)
This article seeks to reconstruct how the process of institutionalization of a presbytery of non-Catholic chaplains developed as a way to adapt and interact with public institutions in Argentina, particularly health care institutions. For this purpose, qualitative interviews with religious actors trained in bioethics were carried out, in addition to participant observation in training spaces and conferences on health and bioethics and documentary analysis of training material and declarations of religious actors on issues of health and bioethics. In a context of relations of asymmetry between the State and the churches and the pluralization of the religious field, diverse needs for spiritual aide in state institutional spaces arise. It is in such a framework that this organization of chaplains gains institutional status, developing its own ethos in search of recognition, visibility and social legitimacy to offer chaplaincy services in institutions where the only chaplains recognized and funded by the State belong to the Catholic religion.